Le rôle de l’aménagement du Saint-Laurent dans l’évolution de la cité de Cornwall (Ontario) - Lasserre, Jean-Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
From the beginning of the 19 th century, the growth of the city of Cornwall bas taken place by spurts, which were connected either with periods of industrialization (1870-1890 and 1920-1930) or, more often, with the construction of canals along the St. Lawrence (1834-1848 and 1876-1908). Canalization work on the river, from 1954 to 1959, brought about to the city a new cyclical spurt, which was reflected in considerable prosperity and speculation during the period of construction, followed by a very distinct depression after 1959, which was made worse by the sudden shutdown of one of the major local plants. However, since 1962, the economic situation has been improving thanks to a new wave of industrialization. The consequence of canalization are no less significant from the standpoint of the organization of urban space. Before the work was carried out, Cornwall’s land use map was already very anarchical. The relocation of transport routes, which was made necessary by the creation of Lake St. Lawrence, has considerably aggravated compartmentalization of the urban space. On the other hand, by contributing to the city's administrative consolidation and to the establishment of its Master Plan, improvement of the river has opened new and more realistic prospects for the city's future growth.